Toward optimization of cyclosporine concentration target to prevent acute graft‐versus‐host disease following myeloablative allogeneic stem cell transplant. Issue 8 (2nd June 2022) - Kwan, Alex Chi Fung; Blosser, Nikki; Ghosh, Sunita; Leyshon, Catherine; Dersch‐Mills, Deonne; Puckrin, Robert; Duggan, Peter; Zepeda, Victor; Savoie, Lynn; Stewart, Douglas; Storek, Jan; Jamani, Kareem
Abstract: Introduction: Despite the common use of cyclosporine (CsA) for acute graft‐versus‐host disease (aGVHD) prophylaxis following allogeneic stem cell transplant, the optimal CsA trough target remains unknown. Materials and Methods: Here, we report on outcomes of adult patients following myeloablative conditioning to identify an optimal CsA trough target and characterize the most relevant timeframe post‐transplant for CsA trough targeting to minimize aGVHD. We retrospectively reviewed 399 consecutive patients who underwent first peripheral blood allogeneic stem cell transplant for hematological malignancies between January 2009 and December 2018. Results: In the unadjusted and adjusted analyses, the incidence of grades 2–4 aGVHD was significantly higher among patients with an average CsA trough concentration <250 mcg/L compared to patients with an average CsA trough concentration ≥250 mcg/L during days 15–28 post‐transplant (31.5% versus 18.8%, P = 0.037), with an odds ratio (OR) of 1.97 (95% confidence interval 1.04–3.71). In contrast, no correlations between CsA trough concentration and relapse, non‐relapse mortality and overall survival was found. Conclusion: In conclusion, early post‐transplant CsA trough concentrations are an important factor in the prophylaxis against aGVHD. Our findings suggest that CsA trough concentrations should be maximized between days 15–28 post‐myeloablative transplant.